Responder
The quadratic function \( y = x^{2} - 6x + 6 \) has a vertex at \( (3, -3) \), opens upwards, and intersects the y-axis at \( (0, 6) \). It also crosses the x-axis at \( x = 3 + \sqrt{3} \) and \( x = 3 - \sqrt{3} \).
Solución
Sure! Let's analyze the quadratic function:
\[ y = x^{2} - 6x + 6 \]
### 1. **Standard Form and Coefficients**
The given equation is in the standard quadratic form:
\[ y = ax^{2} + bx + c \]
Where:
- \( a = 1 \)
- \( b = -6 \)
- \( c = 6 \)
### 2. **Vertex of the Parabola**
The vertex of a parabola defined by a quadratic function can be found using the formula:
\[ x = -\frac{b}{2a} \]
Substituting the values:
\[ x = -\frac{-6}{2 \times 1} = 3 \]
Now, substitute \( x = 3 \) back into the original equation to find the \( y \)-coordinate of the vertex:
\[ y = (3)^2 - 6(3) + 6 = 9 - 18 + 6 = -3 \]
**Vertex:** \( (3, -3) \)
### 3. **Axis of Symmetry**
The axis of symmetry is a vertical line that passes through the vertex:
\[ x = 3 \]
### 4. **Y-intercept**
The y-intercept occurs where \( x = 0 \):
\[ y = (0)^2 - 6(0) + 6 = 6 \]
**Y-intercept:** \( (0, 6) \)
### 5. **X-intercepts (Roots)**
To find the x-intercepts, set \( y = 0 \) and solve for \( x \):
\[ 0 = x^{2} - 6x + 6 \]
Using the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Substituting the coefficients:
\[ x = \frac{6 \pm \sqrt{(-6)^2 - 4(1)(6)}}{2(1)} \]
\[ x = \frac{6 \pm \sqrt{36 - 24}}{2} \]
\[ x = \frac{6 \pm \sqrt{12}}{2} \]
\[ x = \frac{6 \pm 2\sqrt{3}}{2} \]
\[ x = 3 \pm \sqrt{3} \]
**X-intercepts:** \( x = 3 + \sqrt{3} \) and \( x = 3 - \sqrt{3} \)
### 6. **Direction of the Parabola**
Since the coefficient \( a = 1 \) is positive, the parabola opens **upwards**.
### 7. **Graphing the Parabola**
- **Vertex:** \( (3, -3) \)
- **Axis of Symmetry:** \( x = 3 \)
- **Y-intercept:** \( (0, 6) \)
- **X-intercepts:** \( (3 + \sqrt{3}, 0) \) and \( (3 - \sqrt{3}, 0) \)
**Sketch Overview:**
1. Plot the vertex at \( (3, -3) \).
2. Draw the axis of symmetry as a dashed line \( x = 3 \).
3. Plot the y-intercept at \( (0, 6) \).
4. Plot the x-intercepts at \( (3 + \sqrt{3}, 0) \) and \( (3 - \sqrt{3}, 0) \).
5. Draw a symmetric U-shaped curve opening upwards through these points.
### 8. **Summary of Key Points**
- **Vertex:** \( (3, -3) \)
- **Axis of Symmetry:** \( x = 3 \)
- **Y-intercept:** \( y = 6 \)
- **X-intercepts:** \( x = 3 \pm \sqrt{3} \)
- **Parabola Direction:** Opens upwards
If you have a specific aspect of the quadratic function you'd like to explore further (e.g., completing the square, optimization, real-world applications), feel free to ask!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución